EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIO SINIAR TERHADAP KEMAHIRAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMPN 2 TANJUNGPINANG - Tantri, Sriyana; Pujiastuti, Indah; Elfitra, Legi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing skills, particularly in producing observation report texts, remain one of the challenges faced by junior high school students. This condition is reflected in students' difficulties in developing ideas, organizing information systematically, and applying appropriate linguistic conventions. Therefore, this study aimed to determine the effectiveness of the Discovery Learning model assisted by podcast audio media in improving students' observation report writing skills. This research employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The study was conducted with 37 eighth-grade students of SMPN 2 Tanjungpinang selected through purposive sampling. Data were collected through pretest and posttest writing assessments and analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and the N-Gain test with the assistance of IBM SPSS Statistics version 26. The findings revealed a significant improvement in students' observation report writing skills after the implementation of the Discovery Learning model assisted by podcast audio media. The Wilcoxon Signed Rank Test indicated a significance value of 0.000 (p < 0.05), demonstrating a statistically significant difference between students' pretest and posttest scores. Furthermore, the N-Gain analysis showed that the learning model achieved a moderately effective level in enhancing students' writing skills. These findings indicate that integrating the Discovery Learning model with podcast audio media provides an innovative and effective learning alternative for improving observation report writing skills in Indonesian language learning.